Synovial chondromatosis: a rare cause of knee pain and swelling - Bhowmik, Raja; Reddy, Narasimha; Srinivasan, N. (International Journal of Research in Orthopaedics, 2020)
Synovial chondromatosis (SC) is a rare, benign, metaplastic, monoarticular disorder of synovial membrane and bursae of large joints. It commonly affects the large joints such as the knee, hips, wrist, ankle and shoulder. Here we report a case of SC of right knee in a 60-year-old female presenting with chief complaints of pain, swelling, restriction of movement in right knee since 1 year after a fall at home. X-ray of right knee revealed multiple calcified loose bodies. The final diagnosis was established by correlating radiologic findings with the histopathology of the excised specimen. Patient was successfully treated by open partial synovectomy of knee using anterior approach in a single step procedure.